Tensile test and hardness test on FCAW-GS welding results of AB/EH36Z35 material in 3G downhill position - Lubis, Robi Hardi; Gemala, Mega; Kamsyah, Domi; Fyona, Annisa; Saputra, Roni (Journal of Welding Technology, 2024)
Welding is a crucial aspect of the modern construction industry as it allows for efficient and reliable joining of metals. The purpose of this research is to evaluate the FCAW-GS welding process on AB/EH36Z35 material in the 3G downhill position. Additionally, the study aims to analyze the tensile and hardness test results of the welding. The research utilized the FCAW-GS welding method, with tensile testing conducted by the AWS D1.1/D1.1 M:2015 standard. Hardness testing was performed using the Vickers hardness test method with a test load of 10 Kgf, following the ASTM E92:2017 standard. The results of the tensile tests demonstrate that both specimens achieved high tensile strength. Furthermore, the hardness testing indicated no significant changes in material hardness in the HAZ and Line 3 areas. Consequently, this study's findings adhere to the quality standards outlined by AWS D1.1/D1.1M:2015 and ASTM E92:2017, making them a valuable reference for industrial welding processes